The global financial crisis: Countercyclical fiscal policy issues and challenges in Malaysia, Indonesia, the Philippines, and Singapore - Anita Doraisarni (Asian Development Bank Institute (ADBI), 2011)
Several countries have employed countercyclical fiscal policy to ameliorate the impact of the global financial crisis. This study identifies some of the issues and policy implications associated with this policy response in developing countries. Included are case studies of four developing countries in the Asian region - Malaysia, Indonesia, the Philippines, and Singapore. The findings point to a rich diversity in both the size and composition of fiscal stimulus and the challenges which are confronted. This study suggests several steps that countries might take to improve the impact of expansionary fiscal policy in response to future downturns. These include (i) embedding automatic stabilizing impulses through the provision of social safety nets; (ii) increasing tax revenues collected from personal and corporate taxes, by reducing labor market informality through improvements in the business environment; (iii) safeguarding fiscal sustainability; (iv) rebalancing growth by strengthening other sectors of the economy; (v) reducing expenditures on subsidies; and (vi) ensuring smooth and efficient budget execution.
Keywords: E60; E61; E62; E63; 330; Finanzmarktkrise; Antizyklische Finanzpolitik; Wirkungsanalyse; Malaysia; Indonesien; Singapur; Malaysia